2012
DOI: 10.1007/s00221-012-3376-1
|View full text |Cite
|
Sign up to set email alerts
|

Processing of vestibular inputs by the medullary lateral tegmental field of conscious cats: implications for generation of motion sickness

Abstract: The dorsolateral reticular formation of the caudal medulla, the lateral tegmental field (LTF), participates in generating vomiting. LTF neurons exhibited complex responses to vestibular stimulation in decerebrate cats, indicating that they received converging inputs from a variety of labyrinthine receptors. Such a convergence pattern of vestibular inputs is appropriate for a brain region that participates in generating motion sickness. Since responses of brainstem neurons to vestibular stimulation can differ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Fos-ir neurons activated by sinusoidal horizontal rotations were first observed at P4 in several reticular areas that are involved in modulating vestibulo-spinal (Bolton et al 1992;Peterson et al 1980) and autonomic functions (McCall et al 2013;Mori et al 2001): gigantocellular reticular nucleus (Gi) and dorsal paragigantocellular reticular nucleus (DPGi). The number of Fos-ir neurons in these reticular nuclei increased towards the end of the third postnatal week and maintained high in adulthood (Fig.…”
Section: Reticular Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…Fos-ir neurons activated by sinusoidal horizontal rotations were first observed at P4 in several reticular areas that are involved in modulating vestibulo-spinal (Bolton et al 1992;Peterson et al 1980) and autonomic functions (McCall et al 2013;Mori et al 2001): gigantocellular reticular nucleus (Gi) and dorsal paragigantocellular reticular nucleus (DPGi). The number of Fos-ir neurons in these reticular nuclei increased towards the end of the third postnatal week and maintained high in adulthood (Fig.…”
Section: Reticular Nucleimentioning
confidence: 99%
“…Furthermore, medullary reticulospinal neurons were found to regulate vestibulo-respiratory responses (Mori et al 2001). More recently, medullary reticular neurons responding to vertical rotations were also found to be involved in the generation of motion sickness (McCall et al 2013).…”
Section: Sequential Maturation Of the Vestibulo-olivary Pathwaymentioning
confidence: 99%
“…Studies in decerebrate and conscious cats indicated that the responses of many LTF neurons to whole-body rotations in vertical planes are highly complex, and do not reflect a simple integration of signals from otolith organs and semicircular canals (Moy et al 2012; McCall et al. 2013).…”
Section: Brainstem Regions That Participate In Producing Nausea and Vmentioning
confidence: 99%
“…The fraction of neurons with STC responses has been determined in conscious cats for three brainstem areas that participate in generating nausea and vomiting: LTF (McCall et al 2013), the caudal aspect of the vestibular nuclei (Miller et al 2008a), and the rostral fastigial nucleus (Miller et al 2008b). Less than 10% of neurons in the rostral fastigial and caudal vestibular nuclei of conscious cats exhibited STC responses, whereas 25% of neurons in the LTF had such complex responses to vestibular stimulation.…”
Section: Integration Of Labyrinthine and Nonlabyrinthine Inputs By Brmentioning
confidence: 99%
See 1 more Smart Citation